2012
DOI: 10.1029/2012gl051709
|View full text |Cite
|
Sign up to set email alerts
|

Have steering flows in the western North Pacific and the South China Sea changed over the last 50 years?

Abstract: [1] Long-term trends in steering flows over the western North Pacific (WNP) and the South China Sea (SCS) are examined during the peak typhoon season. A nonparametric and robust trend detection method is employed. Both the NCEP and ERA reanalysis data sets suggest a statistically significant decreasing trend in steering flows in the subtropical region of the western WNP (between 120 E or near Taiwan and 145 E) and the northern SCS during 1958-2001. Over this period, the decrease in the WNP is quite large with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 33 publications
5
50
0
Order By: Relevance
“…Chu et al (2012) reported a slowing trend between 1959 and 2009 of the steering fiow in the subtropical westem North Pacific east of Taiwan and the South China Sea in both the National Centers for Environmental Prediction (NCEP)-National Center for Atmospheric Research (NCAR) reanalysis and the 40-yr ECMWF Re-Analysis (ERA-40). Chu et al (2012) reported a slowing trend between 1959 and 2009 of the steering fiow in the subtropical westem North Pacific east of Taiwan and the South China Sea in both the National Centers for Environmental Prediction (NCEP)-National Center for Atmospheric Research (NCAR) reanalysis and the 40-yr ECMWF Re-Analysis (ERA-40).…”
Section: Discnssion and Concluding Remarksmentioning
confidence: 99%
“…Chu et al (2012) reported a slowing trend between 1959 and 2009 of the steering fiow in the subtropical westem North Pacific east of Taiwan and the South China Sea in both the National Centers for Environmental Prediction (NCEP)-National Center for Atmospheric Research (NCAR) reanalysis and the 40-yr ECMWF Re-Analysis (ERA-40). Chu et al (2012) reported a slowing trend between 1959 and 2009 of the steering fiow in the subtropical westem North Pacific east of Taiwan and the South China Sea in both the National Centers for Environmental Prediction (NCEP)-National Center for Atmospheric Research (NCAR) reanalysis and the 40-yr ECMWF Re-Analysis (ERA-40).…”
Section: Discnssion and Concluding Remarksmentioning
confidence: 99%
“…Along a contiguous coastline, strong surges more readily develop due to forced and free coastally trapped waves [ Gill , ], and trends of their intensity and locations can be more easily estimated. We found a significant rise in intensity and northward shift of the location of storm surge, which can be attributed to generally slower‐moving and longer‐lasting storms that also have shifted northward [ Chu et al ., ; Kossin et al ., ]. The trends become significant after 1982, following a rapid increase in the global SST which began in the mid‐1970s [ Nitta and Yamada , ; Trenberth , ].…”
Section: Introductionmentioning
confidence: 98%
“…Changes in the steering flow may be related to changes in the intensity and location of the western North Pacific subtropical high (WNPSH) [ Hu , ; Gong and Ho , ; He and Gong , ; Yang and Sun , ; Lu et al ., ; Wang et al ., ], and recent studies have shown that the WNPSH has weakened and retreated eastward [ Huang et al ., ; Wu and Wang , ]. Weakened steering flow has been attributed to a warming climate since the mid‐1970s to early 1980s by using the reanalysis data [ Wu et al ., ; Tu et al ., ; Chu et al ., ], as well as to future warming in model projection studies [ Murakami et al ., ; He and Zhou , ; He et al ., ]. Evidence of increased preference for typhoons to recurve northward in recent decades is seen in the poleward shift since the late 1970s and early 1980s of the location of intense storm surge along the China coast [ Oey and Chou , ].…”
Section: Introductionmentioning
confidence: 99%